Fresno County Bar Association and Rotary Club Luncheon with State Bar President Anthony Murray - Watkins, Howard::::::::: (1983)
Fresno County Bar Association President Doug Jensen, Rotary Club President and Judge Hollis Best, and David ? Opening the joint luncheon